Racialized landscapes of tourism: from Jim Crow USA to apartheid South Africa - Rogerson, Christian M.; Rogerson, Jayne M. (Bulletin of Geography. Socio-economic Series, 2020)
Tourism studies, including by geographers, give only minor attention to historically-informed research. This article contributes to the limited scholarship on tourism development in South Africa occurring during the turbulent years of apartheid (1948 to 1994). It examines the building of racialized landscapes of tourism with separate (but unequal) facilities for ‘non-Whites’ as compared to Whites. The methodological approach is archival research. Applying a range of archival sources tourism linked to the expanded mobilities of South Africa’s ‘non-White’ communities, namely of African, Coloureds (mixed race) and Asians (Indians) is investigated. Under apartheid the growth of ‘non-White’ tourism generated several policy challenges in relation to national government’s commitments towards racial segregation. Arguably, the segregated tourism spaces created for ‘non-Whites’ under apartheid exhibit certain parallels with those that emerged in the USA during the Jim Crow era.